2006
DOI: 10.1016/j.jasms.2006.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the selective gas-phase fragmentation reactions of methionine side chain fixed charge sulfonium ion containing peptides

Abstract: To enable the development of improved tandem mass spectrometry based methods for selective proteome analysis, the mechanisms, product ion structures, and other factors influencing the gas-phase fragmentation reactions of methionine side-chain derivatized "fixed-charge" phenacylsulfonium ion containing peptide ions have been examined. Dissociation of these peptide ions results in the exclusive characteristic loss of the derivatized side chain, thereby enabling their selective identification. The resultant produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 42 publications
5
28
0
Order By: Relevance
“…However, these competing processes are in fact much higher in energy than typical amide bond cleavages.°For°example,°in°Figure°6°the°typical°energetic requirement to cleave amide bonds or eliminate neutral molecules° [37]°were°included°as°a°band°of°energy between°25°to°40°kcal°mol Ϫ1 .°As°can°be°seen°in°Figure°6, most disulfide bond cleavage processes (S-S and C-S bond cleavage) lie outside the band of energy required to cleave an amide bond in a peptide, with the exception of the salt bridge mechanism to cleave the C-S bond. This is further illustrated in the CID MS/MS fragmentation of the heterodimer of AcCysNHMe-CysNHMe, linked by a disulfide bond (see supplementary Figure S2c).…”
Section: When Will Disulfide Bond Cleavage Occur?mentioning
confidence: 99%
“…However, these competing processes are in fact much higher in energy than typical amide bond cleavages.°For°example,°in°Figure°6°the°typical°energetic requirement to cleave amide bonds or eliminate neutral molecules° [37]°were°included°as°a°band°of°energy between°25°to°40°kcal°mol Ϫ1 .°As°can°be°seen°in°Figure°6, most disulfide bond cleavage processes (S-S and C-S bond cleavage) lie outside the band of energy required to cleave an amide bond in a peptide, with the exception of the salt bridge mechanism to cleave the C-S bond. This is further illustrated in the CID MS/MS fragmentation of the heterodimer of AcCysNHMe-CysNHMe, linked by a disulfide bond (see supplementary Figure S2c).…”
Section: When Will Disulfide Bond Cleavage Occur?mentioning
confidence: 99%
“…CID-MS 3 of the neutral loss product ion from Figure 3a (see Figure 3b) gave rise to a range of sequence-type product ions resulting from cleavages along the peptide backbone, from which the peptide sequence and site of phosphorylation could potentially be derived, together with some relatively low abundance non-sequence-type ions corresponding to losses of the phosphate group and/or water from the precursor or sequence-type product ions. It is expected that as the proton affinity of the product ion structure formed via the loss of dimethylsulfide during CID-MS/MS (previously proposed to be a cyclic iminohydrofuran (IHF) moiety [58, 60]) will be higher than that of an amino group [60], the neutral loss product ion that is initially formed may have decreased proton mobility compared to that of the unmodified peptide of the same charge state. Decreased proton mobility within IHF-modified phosphopeptides could lead to more abundant loss of the phosphate group or increase the potential for phosphate group ‘scrambling’ under CID-MS 3 conditions [12], which therefore could limit the extent of unambiguous sequence information for subsequent phosphopeptide identification and characterization.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that peptides containing ‘fixed charge’ dialkylsulfonium ion derivatives located on selected functional groups of certain amino acids, including the thioether side chain of methionine (formed by reaction with phenacylbromide under acidic conditions) [56-58], the thiol side chain of cysteine (formed by reaction with 3-([ N -bromoacetamido]propyl)-methylphenacylsulfonium bromide (BAPMPS)) [59], or the amino side chain of lysine or peptide N-termini (formed by reaction with S,S ′-dimethylth-iobutanoylhydroxysuccinimide ester (DMBNHS)) [60] all undergo the exclusive neutral loss(es) of dialkylsulfide groups upon CID-MS/MS, independently of the amino acid composition and precursor ion charge state (i.e. ; proton mobility), thereby enabling the selective identification of derivatized peptides from within complex mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen/deuterium exchange can readily be used to differentiate between the charge-remote and charge-directed fragmentation pathways proposed in 5 , and y 6 ions in this spectrum, corresponding to cleavage of the amide bonds adjacent to the site of the cysteine side chain, suggests that the E2 elimination reaction had occurred. However, based on our recent study on the mechanisms responsible for the side-chain fragmentation reactions of methionine fixed charge sulfonium ion-containing peptides, where formation of a mixture of cyclic five-and six-membered product ions were°found°to°be°favored° [19],°the°S N 2 neighboring group participation reactions cannot be ruled out. In°contrast°to°the°data°shown°in°Figure°4a,°b,°and Table°1,°where°the°product°ions°formed°via°the°losses of H 2 NCOCH 2 CH 2 SOH and CH 2 CHCONH 2 (and/or CH 2 CHCONH 2 ϩH 2 O) from the S-amidoethyl cysteine sulfoxide-containing peptides were observed at similar abundances for all the precursor ion charge states examined (i.e., independently of the proton mobility of the peptide ions), the product ion abundances of the side-chain losses from S-pyridylethyl cysteine sulfoxide-containing peptides were observed to vary significantly depending on the proton mobility°of°the°precursor°ion.°For°example,°Figure°6°shows the product ion spectra obtained by CID-MS/MS of the singly, doubly, and triply protonated precursor ions of the S-pyridylethyl cysteine sulfoxide-containing peptide VTMGHFCNFGK [M(ox)C(S-pe) ( (Figure°6b°and°c,°respectively), were observed as the most abundant products.…”
Section: Multistage Tandem Mass Spectrometry H/d Exchange Reactionsmentioning
confidence: 99%